Correlation Analysis of Body Fat Percentage, Muscle Mass, and Bone Mass with Punch Speed in Kumite Karate Athletes - Lita Mulia; Tomoliyus Tomoliyus; Lismadiana Lismadiana; Abdul Alim; Sandi Prayudho; Sri Indah Ihsani; Khairul Azhar Bin Rosawi (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Objective. Anthropometry is recognized as a significant determinant of athletic performance. Despite extensive research on anthropometric factors in conventional sports, limited attention has been given to specific martial arts disciplines, notably in elite karate athletes. Hence, this investigation seeks to explore the correlation between muscle mass, body fat percentage, bone mass, and punch speed among karate athletes. Methods. A total 15 male elite-level karate athletes participated in thsi study. Body weight, body fat percentage, bone mass, and muscle mass were assessed utilizing the Xiaomi Scale 2, whereas punch speed was gauged employing the Hykso Punch Tracker. Results. There was a positive relationship with body fat percentage of 0.679, right speed had a positive relationship with body fat percentage of 0.609, and maximal speed had a negative relationship with body fat percentage of -0.692. While the muscle mass variable shows a correlation value with a left speed of -0.687, at the right speed of -0.616, and at a maximum speed of 0.701. In addition, the bone mass variable has a correlation value with left speed of -0.734, right speed of 0.592, and maximum speed of 0.805. Conclusion. A positive correlation between body fat percentage, muscle mass, and bone mass with punch speed among karate athletes. Athletes exhibiting lower muscle mass and higher body fat tended to demonstrate slower punching speeds. Consequently, the assessment of body fat percentage, muscle mass, and bone mass emerges as a valuable tool for informing the technical aspects of training, particularly in enhancing punch speed for karate practitioners.